2010
DOI: 10.3109/08820538.2010.500210
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Electroretinography

Abstract: Multifocal electroretinography (mfERG) provides functional and objective evidence of retinal dysfunction. We have found mfERG to be especially useful in the management of occult outer retinopathy and Stargardt's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…These results are in agreement to previous works showing that increased CRT severely impairs luminous sensitivity [26,27] and validates MP as a method to demonstrate functional inner retinal impairment in DMO. We also found that mfERG P1 amplitude was likewise significantly and markedly lower in DMO subjects in all studied rings, with an increase of the implicit time, showing functional outer retina impairment [28]. These results confirm the published literature that showed that P1 amplitudes were significantly decreased in DMO patients [19].…”
Section: Discussionsupporting
confidence: 90%
“…These results are in agreement to previous works showing that increased CRT severely impairs luminous sensitivity [26,27] and validates MP as a method to demonstrate functional inner retinal impairment in DMO. We also found that mfERG P1 amplitude was likewise significantly and markedly lower in DMO subjects in all studied rings, with an increase of the implicit time, showing functional outer retina impairment [28]. These results confirm the published literature that showed that P1 amplitudes were significantly decreased in DMO patients [19].…”
Section: Discussionsupporting
confidence: 90%
“… 12 Most studies focused on preoperative and postoperative comparisons, with no comparisons with the fellow eyes or normal controls. 7 , 13 , 14 Our results suggested that the delayed implicit time of all the rings was significantly delayed in the fellow eyes. It revealed that we should be alert to the occurrence of macular holes in the fellow eye.…”
Section: Discussionmentioning
confidence: 50%
“…A number of devices are currently used for healthy and pathological eyes, which include autorefractors, wavefront sensors, slit lamps, scanning laser ophthalmoscopes, and optical coherence tomography (OCT) devices. The state-of-the-art clinical method for an objective measurement of retinal D. Hillmann Thorlabs GmbH, Lübeck, Germany function is electroretinography (ERG) [3]. ERG measures electrical potential changes of photoreceptor cells, inner retinal cells, and ganglion cells in response to specific stimuli.…”
Section: Introductionmentioning
confidence: 99%